Phytoseiidae (Acari: Parasitiformes: Mesostigmata) inhabiting native plants from three biomes in Mato Grosso State, Brazil, with description of a new species - Conceição, Eliziane M.; Demite, Peterson R.; Rezende, José M. [UNESP]; Carniello, Maria A.; Lofego, Antonio C. [UNESP] (Systematic and Applied Acarology Society, 2021)
Phytoseiidae (Acari: Mesostigmata) is one of the most studied mite families due to their use in biological control programs. The southwestern region of Mato Grosso State, Brazil remains poorly explored concerning its mite fauna. Therefore, the aim of this study was to conduct a survey of Phytoseiidae mites in the southwestern region of Mato Grosso State, Brazil. Samplings were carried out in three areas, representing the following: Amazon Forest (AF), Cerrado (CE) and Pantanal (PA) biomes. Five species of native plants commonly found throughout the areas were selected, as well as five others exclusive for each area. In total, five individuals from each plant species were collected. Thirty mite species belonging to 16 genera were recorded: AF (14 species), CE (15) and PA (23). The three most abundant species in this study belongs to the genus Amblyseius: A. acalyphus Denmark & Muma, A. aerialis (Muma) and A. chiapensis De Leon. In the AF the most abundant species were A. aerialis, A. chiapensis and Euseius concordis (Chant); in the CE were A. acalyphus, A. chiapensis and Typhlodromips furcus Lofego, Demite & Feres; lastly in the PA were A. acalyphus, A. aerialis and T. furcus. The plants which harbored the highest richness were common to the three biomes: Physocalymma scaberrimum Pohl (Lithraceae) (12), Cecropia pachystachya Trécul (Urticaceae) (11) and Siparuna guianensis Aubl. (Siparunaceae), (11). A new species, Amblyseius matogrossensissp. nov., is described and illustrated.
Keywords: Amazon Forest; Cerrado; Ecosystem Services; Pantanal; Predators